Sistem Manajemen Percetakan pada CV. Sumber Bahagia Kreasindo Jakarta dengan Metode Prototyping - Umar, Rusydi; P, Purwono; Hafidz, Muhammad Nasir; Hanif, Kharis Hudaibiy; Sakti, Fijaya Bima Dwi; Faroek, Dewi Astria (STIKOM Tunas Bangsa Pematangsiantar, 2020)
Companies that have two or three more people with an agreement between them is the understanding of the Vennootschap Commanditaire (CV). There are various kinds of CVs that are developing at this time, namely agricultural companies, industry, trade, extractives, and service companies. CV. Sumber Bahagia Kreasindo is a company that offers printing services located in Central Jakarta. Increasingly, customers in the company are increasing and expanding, so they need a system that can recapitulate order data from customers to be more efficient and systematic. The rapid development of technology today, so that it can help employees who previously wrote orders manually. Can write orders through the website. The system makes it easy for employees to see the order process from customers,